Business strategies to overcome the crisis: a study in a real estate company in Porto Alegre/RS - Ruwer, Leia Maria Erlich; Kleinowski, Hamilton Luis; Souza, Tayrone Rocha de (Brazilian Journal of Production Engineering, 2021)
This study addresses the topic of Strategic Management and proposes to study business strategies in times of crisis in the real estate industry. It seeks to answer: what business strategies do real estate managers adopt in times of crisis; Thus, the objective proposes to analyze the business strategies of the branch during this period, through the case study of a large real estate company that works with high standard properties, located in Porto Alegre / RS. To make this objective feasible, the theoretical framework was initially approached, addressing the main concepts about strategy (conceptualization, administration and strategic positioning, growth, competitiveness and business strategies in practice, and the delineation of the crisis scenario in the period from 2014 to 2017). As a methodological proposal, the study used exploratory research with a range of qualitative data. The data collection technique used was a semi-structured interview, with content analysis and a non-sample probabilistic. After analyzing the data, it was possible to observe that the responses were unanimous with regard to the rules used in the organization, which forced them to correlate with the theoretical framework addressed, producing as a study professional and demonstrating, mainly, the direction of strategies adopted by the company object of the study.
Keywords: Strategies; Real state market; Administration; Crisis.